2013
DOI: 10.1074/jbc.m113.451948
|View full text |Cite
|
Sign up to set email alerts
|

Link Protein N-terminal Peptide Binds to Bone Morphogenetic Protein (BMP) Type II Receptor and Drives Matrix Protein Expression in Rabbit Intervertebral Disc Cells

Abstract: Background: LPP induces synthesis of aggrecan and collagen II; however, the mechanism is unknown. Results: LPP up-regulated expression of aggrecan, collagen II, and SOX9 through binding to BMP-RII, initiating a complex Smad/BMP feedforward circuit. Conclusion: LPP could promote disc matrix production directly or boost the activity of exogenous BMPs. Significance: LPP may have value in the treatment of degenerated discs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 40 publications
0
52
0
Order By: Relevance
“…20,[29][30][31] It is however, not known whether Link N or MSCs alone can restore the proteoglycan content in larger discs with early degeneration. It is also not known whether a combination of Link N and MSCs would have an additive effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,[29][30][31] It is however, not known whether Link N or MSCs alone can restore the proteoglycan content in larger discs with early degeneration. It is also not known whether a combination of Link N and MSCs would have an additive effect.…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32][33][34] Although Link N is cleaved by AF cells, the resulting N-terminal eight amino acid peptide appears to be proteolytically stable and retains biological activity (unpublished data). Studies utilizing isolated IVD cells in vitro showed that Link N could induce collagen and proteoglycan message levels and result in increased incorporation of radioactive 35 SO 4 into newly synthesized proteoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptic peptides [64] which recruit resident progenitor cells to sites of tissue damage to effect ECM/remodelling to promote repair processes have been described [65] and of relevance to repair of the degenerate IVD. Link-N, a cryptic fragment of linkprotein has been applied to a number of IVD studies and shown to stimulate the resident IVD cell populations as well as progenitor stem cells to upregulate production of collagen and aggrecan and stimulate repair of the degenerate IVD [66][67][68][69][70][71][72]. Future studies will hopefully uncover basic data applicable to the application of the resident progenitor stem cell population we have observed as a therapeutic cell type.…”
Section: Spine Research Issn 2471-8173mentioning
confidence: 99%
“…Hence, Link N is indicated that possesses growth factor -like property. 14 Recently, more and more studies try to use mesenchymal stem cells (MSCs) for further effective treatment, including to enhance TMJ repair. 15,16 MSCs are multipotent stem cells.…”
Section: Introductionmentioning
confidence: 99%